Optimization of Line Cooldown Operations For Ship Readiness In Discharging and Loading on LNG - Muhammad Ardhana Widyapratama; Meilinasari Nurhasanah Hutagaol; Didik Sulistyo Kurniawan (Dinasti Publisher, 2024)
The use of Liquefied Natural Gas (LNG) as an alternative to fuel in the industrial and household sectors has increased rapidly along with the development of science and technology. LNG has an energy density equivalent to conventional fuel but with a lower environmental impact. Even so, the potential hazards of LNG vapor and low temperatures need to be aware of. Nonetheless, LNG has the advantage, such as the use of evaporation as a ship fuel or boil-off gas (BOG). The process of loading LNG to the ship involves several procedures, including cooling pipelines (line cooldown). Cooling pipelines before unloading LNG aims to avoid thermal stress that can damage the pipe. Planning and supervision of pipeline cooling operations become essential to achieve optimal temperature in the pipeline and prevent excessive heel use. Qualitative descriptive research methods are used by collecting data from library studies, documentation, observation, and interviews. In addressing the problem of cooling pipe, optimization of line cooldown operation and heel setting as fuel ship is the focus. The resulting conclusions involve the crew’s understanding of valve function, the duration of the implementation of pipe cooling, the setting of the BOG amount, and the delivery of heel by the Charterer party to the ship. This study resulted in effective and efficient guidance in carrying out line cooldown operations and heel settings. With a better understanding of these factors, ships can optimally run the pipe cooling process, optimize the use of heel, and improve the efficiency of LNG use as a ship’s fuel.